3 - University Expansion and the Challenges to Social Development in Kenya: Dilemmas and Pitfalls - James Jowi; Ibrahim Ogachi Oanda (Journal of Higher Education in Africa, 2012)
The phenomenal expansion of public and private universities in Kenya in recent years has opened access to thousands of knowledge-thirsty stu- dents to achieve their ambitions. Public universities in particular have been forced to diversify their programmes, establish flexible learning schedules and set up campuses away from their traditional locations. But how do cur- rent trends in higher education expansion in Kenya place the institutions in good stead to stem social exclusion and contribute to social development? To what extent is the expansion of public universities in Kenya accompanied by equity considerations and new ways of articulating the issues of class, gender and ethnicity? From being ivory towers and national development projects that were solely seen in terms of workforce development, universi- ties throughout Africa have dispersed to the rural areas both as a strategy to expand access and position themselves as business entities. However, this expansion has not been driven by the public sector. Rather, it has been driven by the private sector, with branch campuses of public universities in rural areas sometimes serving as private income generation units, outside strict public sector oversight. This article traces these developments in Kenya, pointing out the new challenges in terms of equity, quality and the existence of universities as national social institutions that have to be at the centre of social development. The article is based on a critical desk review of pub- lished and grey literature on current trends and implications of public university expansion in Kenya.